2014
DOI: 10.1161/jaha.113.000523
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Based Differences in Outcomes After Percutaneous Coronary Intervention for Acute Myocardial Infarction: A Report From TRANSLATE‐ACS

Abstract: BackgroundData regarding sex‐based outcomes after percutaneous coronary intervention (PCI) for myocardial infarction are mixed. We sought to examine whether sex differences in outcomes exist in contemporary practice.Methods and ResultsWe examined acute myocardial infarction patients undergoing PCI between April 2010 and October 2012 at 210 US hospitals participating in the Treatment with Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events after Acute Coronary Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 48 publications
7
81
0
Order By: Relevance
“…One-year MACE included composite of all-cause death, MI, stroke, or unplanned revascularisation. However, female sex was no longer associated with higher incidence of MACE after multivariable adjustment ( HR 0.98, 95% CI 0.83 to 1.15) 12. While in contrast, a European analysis including 74 389 patients from the French nationwide hospitals database showed that a 30% excess in mortality persists among women even after age and comorbidities are taken into account 3…”
Section: Differences In Outcomes: Is Gender An Independent Prognosticmentioning
confidence: 99%
“…One-year MACE included composite of all-cause death, MI, stroke, or unplanned revascularisation. However, female sex was no longer associated with higher incidence of MACE after multivariable adjustment ( HR 0.98, 95% CI 0.83 to 1.15) 12. While in contrast, a European analysis including 74 389 patients from the French nationwide hospitals database showed that a 30% excess in mortality persists among women even after age and comorbidities are taken into account 3…”
Section: Differences In Outcomes: Is Gender An Independent Prognosticmentioning
confidence: 99%
“…352 Women continue to have almost twice the rate of bleeding after PCI as men. 249,353 It is prudent to pay careful attention by guest on http://circ.ahajournals.org/ Downloaded from to body weight, renal function, and dosing guidelines in women. 349,350 It is also important to continue evaluating for effective strategies to limit post-PCI bleeding in women.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…Studies have reported less use of glycoprotein IIb/IIIa inhibitors, coronary revascularization, and statins at discharge in black versus white and female versus male MI patients. [4][5][6][9][10][11][12] Data also show that, after an initial MI event, black and female patients have greater risk of short-and long-term mortality, recurrent MI, heart failure, and stroke than white and male patients, respectively. 3 In the Medicare population, higher 30-day readmission rates for black versus white MI patients have been observed, 13 whereas, among the younger MI population (<65 years old), women have higher rates of 30-day readmission than men.…”
Section: Discussionmentioning
confidence: 96%
“…Although the incidence of hospitalized MI has decreased over the past 2 decades, rates of decline have been lower for black than for white patients, 3 and racial and sex disparities in the treatment of MI and in clinical outcomes post-MI have been described. [3][4][5][6][7][8][9][10][11][12] Significant differences in 30-day readmissions after MI between races and sexes have also been observed. 13,14 Eliminating such disparities is a national priority, 15 but achieving this goal will require a better understanding of contributing factors.…”
mentioning
confidence: 99%